2014
DOI: 10.1007/s10640-014-9816-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Choices and Hyperbolic Discounting: An Experimental Analysis

Abstract: Environmental goods such as carbon abatement or green space development often generate benefit streams that may not occur until far into the future. How individual consumers value such amenities, therefore, depends critically on the discount rate. The usual assumption is that agents discount future values using constant, exponential rate, but there is some evidence from the lab suggesting that discount functions are more likely quasi-hyperbolic. We compare estimates of subjects' rate of intertemporal time pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
3
31
2
Order By: Relevance
“…This hypothesis was tested across longer delays (i.e., 75 years) than typically used in delay discounting research (e.g., 25 years). We extended the longest delay typically used, as increases or decreases in emissions resulting from decisions or policies that are enacted currently will affect air quality well into the future, and beyond 25 years (i.e., Richards & Green, 2015). …”
Section: Experiments 1 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was tested across longer delays (i.e., 75 years) than typically used in delay discounting research (e.g., 25 years). We extended the longest delay typically used, as increases or decreases in emissions resulting from decisions or policies that are enacted currently will affect air quality well into the future, and beyond 25 years (i.e., Richards & Green, 2015). …”
Section: Experiments 1 Resultsmentioning
confidence: 99%
“…For example, by decreasing delay discounting of air quality and engaging in more future-oriented decision-making, individuals may be more likely to engage in behaviors producing fewer emissions (e.g., riding a bike instead of driving to work) and policy makers may also be more likely to support initiatives that reduce pollution now. Reducing pollution immediately will be critical to produce both immediate and prospective air quality improvements—as carbon abatement and emissions reduction programs frequently produce some benefits that may not occur until far in the future (Richards & Green, 2015). Substantial reductions in emissions will be required to decrease the extensive morbidity resulting from poor air quality such as ischemic heart disease, stroke, lung cancer, and premature death (WHO, 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the nature of the discounted reward, an improvement in air quality for 21 days may seem relatively intangible (and maybe irrelevant) in comparison to receiving (hypothetical) monetary rewards for oneself. However, previous studies showed that temporal discounting occurs when environmental rewards are in question (e.g., air and water quality, Guyse, Keller, & Eppel, 2002;nuclear and hazardous wastes, Moser, Stauffacher, Smieszek, Seidl, Krütli, & Scholz, 2013; improvements in green space and stormwater control as well as reducing greenhouse gasses, Richards & Green, 2015). Furthermore, we did not find an effect of social power on monetary temporal discounting either 2 (see supplementary material available at osf.io/ j67ep).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Rashad (2008) also find a link between time preference and BMI, especially for males, using data from the Behavioral Risk Factor Surveillance System. Richards and Hamilton (2012) also show a positive relationship between discount rates and both drinking and obesity.…”
Section: Literature Reviewmentioning
confidence: 79%
“…They also suggest educational programs to influence individuals' time horizons. Richards and Hamilton (2012) also suggest it might be better to focus anti-obesity policies on informational programs geared to educating individuals about the tradeoffs between short-term gratification and long-term benefits, rather than by taxing certain types of foods. These recommendations tie into our call for more research into understanding the determinants of individual discount rates.…”
Section: Discussionmentioning
confidence: 99%